Nutritional and energy value of Vicia sativa pods (Agroindustrial Science, 2020)
Vicia sativa is one of the most important crops for livestock feed. Pods from Vicia sativa seed production are usually discarded. The objective of this study was to report the nutritional value of Vicia sativa pods. Report of the bromatological analysis was 17.58% for crude protein, 44.96% for neutral detergent fiber, and 55.81% for in vitro dry matter digestibility. Estimates of the energy value on dry matter basis (Mcal kg–1) were made for digestible and metabolizable energy, with values of 2.46 and 2.01, respectively. Vicia sativa pods promise enormous potential as a protein supplement on livestock diets when other sources are not available.